Life cycle assessment of residual forestry biomass chips at a power plant: a Portuguese case study - Ferreira, José (2014)
The residual forest biomass (RFB) sector has been experiencing strong development at European level and particularly in Portugal mainly due to the increase of energy production from renewable sources. The aim of this study is to assess the environmental impacts of eucalyptus RFB chips production chain in Portugal. The environmental and economic impact comparison of the processes included in the production chain is presented as well. The environmental impacts were calculated by the life cycle assessment approach described in the ISO 14040 series of standards. The production chain assessed included all processes from eucalyptus forest until the delivery of RFB chips at the power plant. The main conclusion of this study is that eucalyptus wood production is the process that presents the greatest environmental impact through the product life cycle.